Removal of cationic dye from textile wastewater using treated bagasse fly ash: An industrial waste - Chumpiboon, Areeya; Thongsubsai, Kananan; Pongsiri, Thanatporn; Knijnenburg, Jesper T.N.; Ngernyen, Yuvarat (Engineering and Applied Science Research, 2021)
This study examines the treatment of bagasse fly ash (BFA), a solid waste generated from boilers in the sugar industry, using acid (HCl, H2SO4 and HNO3) treatment and carbonization under N2 atmosphere. The obtained adsorbents were characterized for their porous properties including BET surface area, total pore volume and average pore size. The treated fly ash with the highest surface area (TFA) was studied in detail for its physicochemical properties and the adsorption of methylene blue (MB) dye from aqueous solutions, and was compared with untreated BFA and a commercial activated carbon (CAC). The physicochemical characterization indicated that BFA and TFA represent adsorbents with low and moderate surface area (26 and 239 m2/g, respectively) with functional groups on their surface, while CAC has a high surface area (1130 m2/g) with weak surface functional groups. For all three adsorbents, the MB adsorption equilibrium was attained within 90 min and the kinetic data were best described by pseudo-second order and intra-particle diffusion kinetic models. The adsorption isotherms followed the Langmuir equation with a maximum MB adsorption capacity of 27.2, 39.0 and 42.1 mg/g for BFA, TFA and CAC, respectively. The comparable adsorption capacities of TFA and CAC suggest that the MB adsorption involves both surface area and surface functional groups on the adsorbents. Thus, this study demonstrates that BFA, a low cost solid waste, can be converted by simple treatment into an effective adsorbent for MB removal from aqueous solution with performance comparable to that of high surface area CAC.